Dames, dolls and gun molls the art of Robert Maguire,a retrospective look at the illustrious career of one of the most legendary paperback cover artists of all time - Silke, Jim; Maguire, Robert A. (Milwaukie, Or. Dark Horse Books, 2009)
Best known for his incomparably sexy 'femme fatale' images for pulp paperbacks in the 1950s and 1960s, Robert A Maguire built a long and legendary career showcasing character portraits that were iconic and beautiful, painting subjects that felt simultaneously real and sensually compelling. This book explores the legacy of this artist.
Keywords: Maguire,Robert A; Illustrators -- United States -- Biography; Book covers -- United States -- History; Book covers -- United States -- Catalogs; Pulp literature -- Illustrations -- Catalogs